The Uncommons: An Introduction - Blaser, Mario; de la Cadena, Marisol (Anthropologica, 2017)
This article introduces the term uncommons as a conceptual response to questions that emerged in the context of conflicts around the scale and scope of diverse “commons” that are under threat by extractivism. It introduces the articles for this special issue, which were the result of an invitation to think with the concept of uncommons for a variety of situations. It is concluded that these articles provide a strong grounding to think of uncommons as constitutive of the commons, and that “uncommoning” might be crucial for giving shape to solid commons.